Allies against the rising sun : the United States, the British nations, and the defeat of imperial Japan - Sarantakes, Nicholas Evan, 1966- (Modern war studies., 2009)
This book depicts one of the most detailed assessments ever published of the U.S. alliance with Great Britain, Australia, New Zealand, and Canada against the war with Japan in the Pacific. The author examines Britain's motivations for participating in the invasion of Japan, the roles envisioned by its Commonwealth nations, and the United States' decision to accept their participation. He shows how the interests of all Allies were served by maintaining the coalition, even in the face of disputes between nations. This book takes readers into the halls of both civil and military power in all five nations to show how policies and actions were debated, contested, and resolved. He not only describes the participation of major heads of state, but also brings in lesser-known Commonwealth figures, plus a cast of military leaders including General of the Army Douglas MacArthur and Fleet Admiral Chester Nimitz on the American side, and Admiral of the Fleet Sir Andrew Cunningham along with Field Marshal Sir Alan Brooke on the British side. This book blends the diplomatic, political, and military history of naval, air, and land forces to defeat Japan during World War II.